Pengaruh Tingkat Pendidikan, Pengalaman Kerja Aparatur Desa, dan Pemanfaatan Teknologi Informasi terhadap Pemahaman Laporan Keuangan Desa (Studi Empiris pada Aparatur Desa di Kabupaten Bengkayang) - ernawati, tika (Jurnal KIAFE, 2024)
This study examines the effects of education level, work experience, and information technology utilization on village officials’ understanding of village financial reports in Bengkayang Regency. The study employs a quantitative approach using primary data collected through Likert-scale questionnaires distributed directly to village officials. The sample was selected using purposive sampling and consisted of 45 respondents involved in village financial reporting. Data were analyzed using descriptive statistics, data quality tests, classical assumption tests, multiple linear regression, and hypothesis testing with SPSS. The results indicate that education level and information technology utilization have no significant effect on the understanding of village financial reports, while work experience has a positive and significant effect. Simultaneously, education level, work experience, and information technology utilization significantly affect the understanding of village financial reports. The adjusted coefficient of determination is 30.3%, indicating that the three independent variables explain 30.3% of the variation in village financial report understanding.